2009
DOI: 10.1111/j.1365-2591.2008.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

New dimensions in endodontic imaging: Part 2. Cone beam computed tomography

Abstract: Cone beam computed tomography (CBCT) has been specifically designed to produce undistorted three-dimensional information of the maxillofacial skeleton, including the teeth and their surrounding tissues with a significantly lower effective radiation dose compared with conventional computed tomography (CT). Periapical disease may be detected sooner using CBCT compared with periapical views and the true size, extent, nature and position of periapical and resorptive lesions can be assessed. Root fractures, root ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
277
1
39

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(338 citation statements)
references
References 45 publications
2
277
1
39
Order By: Relevance
“…CBCT images overcome the limitations of 2D images including the lack of the buccolingual dimension, masking of areas of interest by overlying anatomy (anatomic noise), and avoiding geometric distortion. A high spatial resolution and true volumetric information can be obtained because of the isotropic nature of CBCT images (16,30). Moreover, it has been shown that dental trauma and developmental anomalies can be better assessed in 3 dimensions (16,(30)(31)(32).…”
Section: Clinical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT images overcome the limitations of 2D images including the lack of the buccolingual dimension, masking of areas of interest by overlying anatomy (anatomic noise), and avoiding geometric distortion. A high spatial resolution and true volumetric information can be obtained because of the isotropic nature of CBCT images (16,30). Moreover, it has been shown that dental trauma and developmental anomalies can be better assessed in 3 dimensions (16,(30)(31)(32).…”
Section: Clinical Researchmentioning
confidence: 99%
“…A high spatial resolution and true volumetric information can be obtained because of the isotropic nature of CBCT images (16,30). Moreover, it has been shown that dental trauma and developmental anomalies can be better assessed in 3 dimensions (16,(30)(31)(32). Nevertheless, CBCT imaging has its own limitation; the effective radiation dose delivered by CBCT devices available in the market varies enormously from around 10-1200 mSv (which is an equivalent of 2-240 panoramic radiographs) (33,34).…”
Section: Clinical Researchmentioning
confidence: 99%
“…The major advantages of cone beam computed tomography over spiral computed tomography are the reduced radiation exposure and a superior image quality. 7 However, spiral computed tomography scan was used for the diagnosis of present case due to unavailability of cone beam computed tomography in the city at the time when patient reported.…”
Section: Discussionmentioning
confidence: 99%
“…When the preoperative radiograph and above characteristic clinical examinations under the DOM still cannot make it clear, CBCT should be taken into consideration. It can provide 3-D image and help the clinicians to evaluate the root canal system at different levels [18]. The difficulty of cleaning, shaping and obturation should be the narrow structures such as isthmus, trough and fin.…”
Section: Discussionmentioning
confidence: 99%